Contempt of Court dalam Pelaksanaan Putusan PTUN: Suatu Perbandingan Indonesia dan Prancis - Fajar Rachmad Dwi Miarsa; M Zamroni; Ahmad Heru Romadhon; Cholilla Hazir Adhaningrum (Fakultas Hukum, Universitas Internasional Batam, 2021)
The aim of comparing the TUN judicial system in France with the Indonesian state is to provide an analysis of the competence of state administration justice in France (its administrative court), particularly regarding the administrative or technical implementation of the judiciary. This can provide direction for the ius constituendum in the competence of the Indonesian State Administrative Court, as well as explain contempt of court actions in the implementation of TUN Judicial decisions between Indonesia and France. The research was conducted using a normative juridical approach and has a literary nature. The Indonesian state administration court system still expects an ius constituendum regarding contempt of court regulation. The French state is known as a country that has judicial authority in the world so that the French state does not recognize contempt of court in the application of the TUN court decision.